Natural History of Diabetic Retinopathy Through Retrospective Analysis in Type 2 Diabetic Patients—An Exploratory Study - Mehak Gupta (Frontiers Media S.A., 2021)
Background and Aims: Diabetic retinopathy is the most common diabetes-associated microvascular complication and is among the leading causes of vision loss or blindness in the adult population. The present study is a retrospective study that reported the natural history of diabetic retinopathy.Methods: Retrospective medical records of 170 patients aged > 20 years with a confirmed complication of diabetic retinopathy were recruited into the present study. A questionnaire was also sent to each subject for gathering their experiences, and verification was done by the attending medical physicians. The questionnaire was answered by all recruited patients.Results: The results showed that 23 (13.5%) subjects have a family history of diabetic retinopathy with 10 (5.9%) having mild NPDR, 63 (37.1%) with moderate NPDR, 60 (25.3%) have severe NPDR while 37 (21.8%) have PDR complications. The presence of co-morbidities was found in 139 (81.8%) subjects. Patients with PDR reported a significantly longer duration of diabetes mellitus with worse glycemic control.Conclusions: The study revealed and concluded that adherence to the prescribed management regimen is important, for which patient education was the key which was lacking.